Study guides

☆☆

Q: P equals 3a-3q then 6a equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

6a - 4 = -2(+ 4 on both sides)6a = 2(divide both sides by 6)a = 2/6a = 1/3

9a = 6a + 4 subtracting 6a from each side, 3a = 4 dividing each side by 3, a = 4/3

6a2

The solution for the value of 3a would be -3. The equation would be 6a + 3(4) = 2.

v equals m divided by p

Related questions

If 6a divided by 2 equals 12 then A equals

-6a + 8 = 2 -6a = -6 a = 1

5a+5=6a-7

If you mean: 15a = 6a - 90 then the variable a works out as -10. If you mean 15a + 6a - 90, then it equals 21a - 90.

36

6a-10a=16 -4a=16 a=-4

6a - 13 = -5 Therefore, 6a = 8 a = 8/6 a = 1.3 recurring (that is, 1.3333..)

If 6A - 58 = 44 then 6A = 102 making A = 17.

6a + (7b - 4a - 8b) = (6a - 4a) + (7b - 8b) = 2a - b

10a-37=6a+51 -6a -6a subtract 6a from both sides and the 6a's cancel 4a-37=51 +37 +37 4a=88 /4 /4 a=22

6a - 4 = -2(+ 4 on both sides)6a = 2(divide both sides by 6)a = 2/6a = 1/3

6a-3=8a+11 -3-11=8a-6a -14=2a a=-7

People also asked